Electric Gamelan Kit: GAME SIMULASI ALAT MUSIK PUKUL TRADISIONAL MENGGUNAKAN LEAPMOTION CONTROLLER - Fitria, Citra P (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
Electric Gamelan Kit is a simulation game of traditional musical instruments from Central Java Bonang which uses the latest technology that is Leapmotion Controller based Desktop. This game is one of the first steps to preserve Indonesian culture, especially traditional musical instrument at Central Java. This game is equipped with regional song instrument from Central Java that is Lir-ilir and Gundul-Gundul Pacul. To play it just needs to move your hand (as well as hitting) you above the Leapmotion controller sensor. If you can get through it well the score will continue to grow.